Vertical Skeletal Changes after Extraction and Nonextraction Orthodontic Treatment - Shafique, Hafiza Z.; Zaheer, Rumeesha; Jan, Abdullah; Mughal, Alaina T.; Shahid, Rooma; Ghaffar, Fareena; Zahoor, Tooba; Mehmood, Sundas; Nawaz, Ramsha; Umar, Safia; Hassan, Mehak; Mudasser, Muhammad A. (European Journal of Dentistry, 2022)
Objectives Due to the constant battle regarding the controversial topic of orthodontic extraction, this study aims to assess the changes in vertical dimensions of patients treated with premolar extractions compared with nonextraction orthodontic patients.Materials and Methods A sample of 60 borderline patients were recruited and divided into extraction and nonextraction groups. Eleven pretreatment cephalometric measurements were recorded using WebCeph and patients were followed-up until the completion of treatment.Statistical Analysis Intragroup and intergroup comparisons were made using paired t-test and two-sample independent t-test, respectively. The joint significance of differences was measured using F-tests.Results The intragroup comparison revealed that in the extraction group, the vertical dimension was significantly increased posttreatment for four cephalometric measurements, that is, mandibular plane angle (p < 0.05), palatal plane angle (p < 0.05), Frankfort mandibular plane angle (p < 0.05), and y-axis (p < 0.05). In the comparison of the posttreatment values of both groups, the mean differences of the posttreatment values for sella nasion (SN)-gonion (Go)-gnathion (Gn) angle (p = 0.008), the total anterior (p = 0.050), and lower anterior facial heights (AFH; p = 0.011) were significantly higher. At the same time, the Jarabak ratio was significantly (p = 0.006) lower in the extraction group than in the nonextraction group.Conclusion The increase in vertical dimension is significantly higher in the extraction group than in the nonextraction group which indicates a significant impact of orthodontic extraction on the vertical dimensions.
Keywords: orthodontic space closure; vertical dimensions; cephalometry/methods; artificial intelligence